Sovereign Sukuk for Financing the Public Budget Deficit "Sukuk Al-Ijara" in Morocco: الصكوك السيادية لتمويل عجز الميزانية العامة "صكوك الإجارة" بالمغرب - Jihaoui, Maroua El (Jurnal Iqtisad, 2024)
Sovereign sukuk play an essential role in providing effective and sustainable financing for the government's expenditures and investment projects, while maintaining fiscal discipline by limiting the accumulation of public debt. Among these sukuk, we find Ijara sukuk as one of the recently developed financial instruments utilized by governments and companies to fund their projects and meet financial needs. In particular, Ijara sukuk have become increasingly prevalent in Morocco, where they play a pivotal role in funding public budget deficits and supporting the national economy. This study aims to highlight the importance of sovereign bonds in Morocco, with a particular focus on Ijarah bonds, as one of the emerging and important financial instruments in attracting savings and mobilizing the necessary funds to finance investment projects. Furthermore, the study aims to illustrate the high efficiency and efficacy of these instruments in financing public budget deficits. This is accomplished through the utilization of descriptive and analytical methodologies, which have been demonstrated to be effective in achieving the desired objectives. The study concludes that sovereign bonds, particularly Ijarah bonds, are an important instrument for achieving fiscal balance due to their distinctive features and attributes that differentiate them from other financial instruments. Sukuk negara memainkan peran penting dalam menyediakan pembiayaan yang efektif untuk memenuhi kebutuhan pemerintah di bidang pengeluaran publik dan proyek-proyek investasi tanpa harus menambah utang publik. Di antara sukuk-sukuk ini, kami menemukan sukuk Ijara sebagai salah satu instrumen keuangan baru yang digunakan oleh pemerintah dan perusahaan untuk mendanai proyek-proyek mereka dan memenuhi kebutuhan keuangan, terutama di Maroko, di mana sukuk Ijara memainkan peran yang semakin penting dalam mendanai defisit anggaran publik dan mendukung perekonomian nasional. Studi ini bertujuan untuk menyoroti pentingnya obligasi negara di Maroko, terutama obligasi Ijarah, sebagai salah satu instrumen keuangan yang sedang berkembang dan penting dalam menarik tabungan dan memobilisasi dana yang diperlukan untuk membiayai proyek-proyek investasi. Studi ini juga berusaha untuk menunjukkan efisiensi dan kemampuan yang tinggi dari instrumen-instrumen ini dalam membiayai defisit anggaran publik. Hal ini dicapai dengan menggunakan pendekatan deskriptif dan analitis yang dianggap efektif dalam mencapai tujuan yang diinginkan. Studi ini menyimpulkan pentingnya obligasi negara, khususnya obligasi Ijarah, dalam mencapai keseimbangan fiskal, karena fitur dan atribut unik yang membedakannya dari instrumen keuangan lainnya. يعتبر التمويل المستدام لعجز الميزانية العامة أمرا ضروري لاستقرار الاقتصاد الوطني وتحقيق التنمية المستدامة،  وفي هذا السياق تلعب الصكوك السيادية دورا مهما في توفير تمويل فعال لتلبية احتياجات الحكومة في مجالات النفقات العامة والمشاريع الاستثمارية دون اللجوء إلى زيادة الدين العام، ومن بين هذه الصكوك نجد صكوك الإجارة بوصفها واحدة من الأدوات المالية المستجدة التي تستخدمها الحكومات والشركات لتمويل مشاريعها وتلبية الاحتياجات المالية خاصة في المغرب، حيث باتت صكوك الإجارة تلعب دورا متزايد الأهمية في تمويل عجز ميزانية العامة ودعم الاقتصاد الوطني. تهدف هذه الدراسة إلى إظهار الأهمية التي تحظى بها الصكوك السيادية بالمغرب خاصة صكوك الإجارة باعتبارها من بين الأدوات المالية المستجدة والمهمة في اجتذاب المدخرات وتجميع الأموال اللازمة لتمويل المشروعات الاستثمارية، وكدى لما تتميز به من كفاءة وقدرة عالية على تمويل عجز الميزانية العامة، كل هذا من خلال الاعتماد على المنهج الوصفي و التحليلي باعتبارهما كفيلين لتحقيق الأهداف المتوخاة، وتوصلت الدراسة إلى أهمية الصكوك السيادية وخاصة صكوك الإجارة في تحقيق الموازنة العامة، وذلك لما تمتلكه هذه الأداة المالية من مميزات ومقومات تميزها عن غيرها من الأدوات. الكلمات المفتاحية: الصكوك السيادية، عجز الميزانية العامة، صكوك الإجارة، التمويل، المغرب